Diagnosis of pediatric anti-NMDAR encephalitis at the onset: A clinical challenge. (January 2021) - Ursitti, F.; Roberto, D.; Papetti, L.; Moavero, R.; Ferilli, M.A.N.; Fusco, L.; Vigevano, F.; Curatolo, P.; Valeriani, M.
Abstract: Backgrounds: To investigate the clinical and instrumental features at the onset addressing to the diagnosis of anti-NMDAR encephalitis. Methods: Twenty children (age: 15 months-17 years; 7 males, 13 females) with initial suspected diagnosis of autoimmune encephalitis, observed between January 2008 and March 2018, were included. The final diagnosis was anti-NMDAR encephalitis in 7 children, other/probable autoimmune encephalitis in 7 children, and primary psychosis in the remaining 6 children. Results: At the clinical onset, anxiety disorder was the main symptom that helped in distinguishing the group of psychotic children from children with non-infectious encephalitis (P = 0.05 OR = 0.001), while epileptic seizures strongly predicted anti-NMDAR encephalitis (P = 0.04 OR = 28.6). At the onset, anti-NMDAR encephalitis could be distinguished from other/probable autoimmune encephalitis for the presence of sleep/wake rhythm alteration (P = 0.05 OR = 15). Among the symptoms occurring during the hospitalization, movement disorders (P = 0.031 OR = 12) were predictive of non-infectious encephalitis rather than primary psychosis. More specifically, the occurrence of language impairment (P = 0.03 OR = 33), epileptic seizures (P = 0.04 OR = 28.6) and catatonia (P = 0.03, OR = 33), were predictive of anti-NMDAR encephalitis. Also at this stage, anxiety disorder (P = 0.03 OR = 0.033) was predictive of primary psychosis. Conclusion: Our findings suggest that at the clinical onset epileptic seizures and sleep/wake rhythm alteration represent the main features addressing to the diagnosis of anti-NMDAR encephalitis rather than primary psychosis and other/probable autoimmune encephalitis, while anxiety disorder could be a solid predictor of primary psychosis. Highlights: Clinical presentation of pediatric anti-NMDAR encephalitis and psychosis can be overlapping. Epilepsy and sleep/wake rhythm abnormalities characterize anti-NMDAR encephalitis onset. Anxiety disorder is a strong predictor of psychosis. Normal brain MRI does not exclude anti-NMDAR encephalitis. CSF oligoclonal bands are more frequent in anti-NMDAR than other autoimmune encephalitis.